2015
DOI: 10.1080/01402382.2015.1116199
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality, ideology and party positions towards European integration

Abstract: The rise of political contestation over European integration has led many scholars to examine the role that broader ideological positions play in structuring party attitudes towards European integration. This article extends the existing approaches in two important ways: 1) It shows that whether the dimensionality of politics is imagined in a one dimensional 'general left-right' form or a two dimensional 'economic left-right/social liberal-conservative' form leads to very different understandings of the way id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 51 publications
1
24
1
Order By: Relevance
“…Research has shown that, in the case of mainstream parties in the UK, there is a significant negative relationship between social conservatism and support for EU integration (Hooghe, Marks, & Wilson, 2004;Prosser, 2016). To explain the rising support of right-wing populism in the UK, Ford and Goodwin (2014) note that UKIP's appeal stems from three motives: a hard brand of Euroscepticism, a strong opposition to immigration and a dissatisfaction with the established political parties.…”
Section: The Big Five Model Of Personalitymentioning
confidence: 99%
See 4 more Smart Citations
“…Research has shown that, in the case of mainstream parties in the UK, there is a significant negative relationship between social conservatism and support for EU integration (Hooghe, Marks, & Wilson, 2004;Prosser, 2016). To explain the rising support of right-wing populism in the UK, Ford and Goodwin (2014) note that UKIP's appeal stems from three motives: a hard brand of Euroscepticism, a strong opposition to immigration and a dissatisfaction with the established political parties.…”
Section: The Big Five Model Of Personalitymentioning
confidence: 99%
“…Relationships between political orientation and both agreeableness and extraversion appear less frequently in research, although agreeableness has been observed to have a negative but weak correlation with conservatism. Given the negative relationship between social conservatism and support for EU integration (Hooghe et al, 2004;Prosser, 2016), a reasonable hypothesis is that Leave voters will, as a population, display higher conscientiousness together with lower openness, neuroticism and agreeableness than Remain voters.…”
Section: The Big Five Model Of Personalitymentioning
confidence: 99%
See 3 more Smart Citations